A Result in Dislocated Quasi Metric Space - Panthi, D.; Jha, K. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
In this paper, we prove a fixed point theorem in dislocated quasi-metric space which extends and unifies some well-known similar results in literature.